A Comparison of Use Topography and Nicotine Pharmacokinetics Among Loose and Portioned Smokeless Tobacco Users. Issue 4 (15th August 2022) - Nighbor, Tyler; Meredith, Steven; Salazar, Esther; Cartagena, Casandra; Koszowski, Bartosz; Pickworth, Wallace B; Hull, Lynn C
Abstract: Introduction: Moist snuff smokeless tobacco (ST) products are available in the United States in both "loose" and "portioned" (ie, pouched) formats, but no published study to date has clinically evaluated the associations between ST format, use behavior, and nicotine exposure. Aims and Methods: Participants used their usual brand of ST (loose ST [ n = 30] or portioned ST [ n = 20]) during an experimental visit wherein use behavior and plasma nicotine pharmacokinetic parameters were measured following single use (first hour of the session) and ad libitum use (remaining 7 h of the session). Participants' ST products were chemically characterized prior to use for pH and nicotine content. Results: The average amount per use (2.99 vs. 1.52 g; p = .005) and total amount used (11.45 vs. 5.4 g; p = .002) were significantly higher among the loose ST group. Maximum plasma nicotine concentration ( C max ; 33.4 vs. 19.1 ng/ml) and area under the nicotine concentration versus time curve (AUC) were significantly higher for the loose ST group for the first hour (1474.8 vs. 807.2 min* ng/ml; p = .003) and throughout the 8-hour session (15827.9 vs. 8155.3 min* ng/ml; p < .001). Significant associations were observed between free nicotine content and first use C max ( r s = .488, loose ST group) and AUC0–1 h ( r s = 0.448, loose ST group; r s = .441, portioned ST group). Conclusions: The loose ST group used more product and had a greater average deposition time per use than the portioned ST group. Nicotine exposure was more strongly associated with free nicotine content than total nicotine content. Implications: To our knowledge, the current investigation was the first study to date to clinically evaluate the associations between usual-brand smokeless format, use behavior, and nicotine exposure. We observed meaningful differences in use behavior and subsequent nicotine exposure between loose and portioned ST users. Further, we observed that nicotine exposure was more strongly associated with free nicotine content than total nicotine content.